Ancient melt extraction from the oceanic upper mantle revealed by Re-Os isotopes in abyssal peridotites from the Mid-Atlantic ridge - Harvey, J; Gannoun, A; Burton, K; Rogers, N; Alard, O; Parkinson, I (2006)
Comprehensive major-, trace-element and rhenium-osmium (Re-Os) isotope data are presented for abyssal peridotites from Ocean Drilling Program (ODP) Leg 209, in the North Atlantic. The samples are from a single core (Site 1274A) located on the western wall of the axial rift valley of the Mid-Atlantic ridge, and their study allows elemental and isotope information to be precisely related to spatial variations in primary lithology, serpentinisation and seafloor weathering. The harzburgites and dunites at this site are highly serpentinised (with the degree of serpentinisation increasing with depth below the sea floor). Petrographic observations and variations of fluid mobile elements (such as Ba, Sr, U, and Re) are consistent with seawater interaction in the upper part of the core. Nevertheless, major and trace element indicators of the extent of melt depletion indicate extreme melt loss, and suggest that these are amongst the most depleted abyssal peridotites recovered thus far. Despite the evidence for extensive serpentinisation and sea floor weathering all of the samples possess 187Os/188Os isotope compositions that are less radiogenic than estimates for the primitive upper mantle (PUM), lower than any yet reported for abyssal peridotites, and consistent with melt loss over, at least, the past 1.5 Ga. Single sulphide Re-Os data show evidence for recent recrystallisation or diffusional modification either due to partial melting or seawater alteration. However, some grains are extremely unradiogenic (187Os/188Os = 0.114) providing unequivocal evidence for at least some degree of melt depletion at ca. 2 Ga. Taken with recently published data these results suggest that ancient melt depletion may be a widespread feature of the oceanic upper lithosphere, even though evidence for this depleted reservoir has not yet been observed in the Re-Os chemistry of mid-ocean ridge basalts. © 2006 Elsevier B.V. All rights reserved.